A comparabilidade das escolhas contábeis na mensuração subsequente de ativos imobilizados, de ativos intangíveis e de propriedades para investimento - Souza, Flaida Êmine Alves de (2014)
The expertise comparability, accounting choices and fair value is one of the most controversial and needy subjects of discussions in the current accounting scene. The accounting choices are necessary for the faithful representation is guaranteed, while his discretionary use may reduce comparability, which is expected by the IASB. When the accounting choices refer to the choice of the methods of historical cost and fair value, controversies are even greater. As a result, this study identified the comparability degree of accounting choices in the subsequent measurement of property, plant and equipment, intangible assets and investment property for publicly-held companies belonging to Brazil, Chile and Peru. It also investigated the characteristics that may influence the accounting choices of managers from these entities. The T Index was used to calculate the comparability, and in order to verify the explanatory variables the Logit/Probit regressions were estimated, both the periods from 2009 to 2013. As a result, it was found that for property, plant and equipment the national and international comparability increased with the adoption of International Financial Reporting Standards (IFRS) and remained increased over time. In sectorial analysis, virtually all sectors had a high comparability after IFRS adoption. This fact was due to the majority of (or all) the entities have opted for the method of historical cost in the subsequent measurement of these assets. Regarding the explanatory variables, it was found that the country, the profitability, the relevance, the sector of activity and the time may influence the accounting choices of managers. For intangible assets, the national and international comparability were already high before the adoption of IFRS and further increased after adoption. In sectorial analysis, it were identified comparability indexes even higher compared to the ones from the group of countries, because virtually all sectors showed comparability with maximum values. This result was due to the vast majority of organizations which have chosen the method of historical cost for subsequent measurement of intangible assets. Concerning the explanatory variables, it was found that big four, size and relevance influenced the accounting choices of managers. For investment property, the national and international comparability did not increase with the adoption of IFRS, remaining with rates near 0.50 (low comparability) in practically all fiscal years. These results are due to the fact that managers choices divide between the method of historical cost and fair value. In the sectorial analysis, although some sectors show maximum comparability in all investigated periods, others obtained a low/moderate comparability in practically all years. Through regression analysis, it was found that the variables big four, relevance, indebtedness, country and sector of activity influenced the accounting choices of managers in the subsequent measurement of investment properties. Thus, the simple adoption of IFRS does not guarantee the comparability. When considering the non-disclosure of information as another possible accounting choice for managers, the national and international comparability decreased by country and by sector. It is noteworthy, therefore, the importance of disclosure of financial information, because the non-disclosure affects comparability.